IoT-based high-accuracy monitoring system for on-grid photovoltaic power system using NodeMCU ESP8266 and PZEM004T - Wibowo, Lastoni; Wahyusari, Retno; Yuwono, Teguh; Shofia, Aina (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2024)
Monitoring systems for On-Grid Photovoltaic Power Systems use IoT technology for real-time performance tracking via the Internet. Typically, these systems involve current and voltage sensors to measure Current, Voltage, Power, Energy, and Power Factor (Cos φ). However, many existing systems do not thoroughly address the accuracy of these measurements. To ensure reliability, a system must achieve measurement accuracy above 90%. This article presents an IoT-based On-Grid photovoltaic power monitoring system designed to measure electrical parameters with high accuracy. The system uses the PZEM004T sensor and NodeMCU ESP8266, which transmits data to the Blynk IoT server over an internet connection. The system's accuracy is assessed using the Mean Absolute Percentage Error (MAPE) calculation. Results show that this system achieves an accuracy of 96.37%, indicating high reliability and suitability for practical use due to its accuracy above 95%. This makes the designed system highly reliable, effective, and feasible for monitoring On-Grid Photovoltaic Power Plants.